2022
DOI: 10.1007/s13593-022-00832-1
|View full text |Cite
|
Sign up to set email alerts
|

Cereal species mixtures: an ancient practice with potential for climate resilience. A review

Abstract: Food security depends on the ability of staple crops to tolerate new abiotic and biotic pressures. Wheat, barley, and other small grains face substantial yield losses under all climate change scenarios. Intra-plot diversification is an important strategy for smallholder farmers to mitigate losses due to variable environmental conditions. While this commonly involves sowing polycultures of distinct species from different botanical families in the same field or multiple varieties of the same species (varietal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…Meta‐analyses of the benefits of variety mixtures have indeed shown that (i) variety mixtures often have higher yields than their respective pure stands (overyielding), albeit average benefits are relatively minor, for example, approximately 2% –4% in wheat; (ii) mixtures are effective in suppressing disease epidemics, and overyielding strongly increases under high disease pressure, and (iii) yield stability is often slightly higher in variety mixtures (Borg et al., 2018; Kristoffersen et al., 2020; Kiær et al., 2009; Reiss & Drinkwater, 2018; Smithson & Lenné, 1996). Furthermore, mixtures may buffer effects from environmental influences and tend to show a higher resilience (McAlvay et al., 2022). Importantly, these identified benefits can be expected to occur on average in any random mixture, and even without prior knowledge of the potential drivers of positive mixture effects.…”
Section: Introductionmentioning
confidence: 99%
“…Meta‐analyses of the benefits of variety mixtures have indeed shown that (i) variety mixtures often have higher yields than their respective pure stands (overyielding), albeit average benefits are relatively minor, for example, approximately 2% –4% in wheat; (ii) mixtures are effective in suppressing disease epidemics, and overyielding strongly increases under high disease pressure, and (iii) yield stability is often slightly higher in variety mixtures (Borg et al., 2018; Kristoffersen et al., 2020; Kiær et al., 2009; Reiss & Drinkwater, 2018; Smithson & Lenné, 1996). Furthermore, mixtures may buffer effects from environmental influences and tend to show a higher resilience (McAlvay et al., 2022). Importantly, these identified benefits can be expected to occur on average in any random mixture, and even without prior knowledge of the potential drivers of positive mixture effects.…”
Section: Introductionmentioning
confidence: 99%
“…Such a design can also be of interest to study intercropping, as long as the plants are easily separable to be phenotyped individually. This should be the case of mixtures of cereals (McAlvay et al, 2022), but not of some cereal-legume mixtures such as those with vining cultivars of field pea whose tendrils coil around neighboring plants, allowing them to climb and use them as support (Podgórska-Lesiak and Sobkowicz, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable Livelihoods is a newish term but probably an ancient idea, which draws from; resonates with ancient practices in the occupation of farming for a livelihood. This included practices such as multi-cropping, for instance, cereal-mixing, in which multiple seeds planted at the same time also provided protection when one of them was attached by a bug, or a drought, or a flood (McAlvay et al, 2022). The job is a form of monocropping, which works well only until the first bug comes along, and then all is all too readily lost.…”
Section: Sustainable Livelihoods!mentioning
confidence: 99%